Healthcare Services for Spectators during the FIFA World Cup 2022TM - Muhammad Arsalan Zamir (18466355) (2024)
Background Players are often viewed as the single-most important participants in a FIFA World CupTM, but in fact spectators make it a global spectacle. Qatar received 1.4 million visitors during the FIFA World Cup 2022TM, a 50% increase in population. The aim was to provide high quality medical care to the visiting spectators, while continuing regular medical services for residents. This presentation overviews the challenges and solutions when hosting the world’s largest sporting event. Methods This is a case study of the planning and provision of spectator healthcare services during the FIFA World Cup 2022TM. Results There were additional clinics setup for the tournament, majority located in the stadiums for match days (85 clinics) and 30 clinics at other sites, including official hotels and fan villages. Each clinic was staffed by a physician and nurse while paramedic teams ensured prompt assessment and management of first aid and emergency situations in the stadiums and fan areas. Stadium teams were deployed to cover two stadiums according to tournament schedules. In addition, a central workforce hub was setup to provide central coordination of all workforce related issues, including rostering, training, transport and accreditation issues. An important component of smooth clinic functioning included a standardised inventory for all tournament clinics, which were proactively restocked with medical supplies using an electronic management system supported by a central logistics hub. Conclusion The provision of healthcare services throughout the FIFA World CupTM was undertaken to a very high standard, acknowledged by the various stakeholders involved. The central theme was teamwork and coordination between the involved stakeholder organisations along with their representative deployed staff. The arrangement to utilise one medical team to cover two stadiums was a core factor in being able to successfully prepare and execute the delivery of high-quality healthcare for visitor and residents alike